Pre-operative Hemostatic Status in Dogs Undergoing Splenectomy for Splenic Masses - McPhetridge, Jourdan B.; Lynch, Alex M.; Webster, Cynthia R. L.; McCobb, Emily; de Laforcade, A. M.; O'Toole, Therese E. (Frontiers in Veterinary Science, 2022)
Portal system thrombosis is a rare but potentially fatal complication of splenectomy in dogs. The mechanism behind development of post-operative portal system thrombosis is unclear but may include alterations of portal blood flow following surgery, acquired hypercoagulability and endothelial dysfunction. The aim of the study was to evaluate hemostatic biomarkers in hemodynamically stable (heart rate <130 beats/min, blood lactate < 2.5 mMol/L) and non-anemic (hematocrit >35%) dogs prior to splenectomy for splenic masses. Our hypothesis was that this population of stable dogs would have pre-existing laboratory evidence of hypercoagulability unrelated to shock, bleeding, anemia, or other pre-operative comorbidities. Pre-operatively, abdominal ultrasonography was performed and blood was collected for platelet enumeration, prothrombin time (PT), activated partial thromboplastin time (aPTT), kaolin-activated thromboelastography (TEG), fibrinogen, von Willebrand factor activity (vWF:Ag), antithrombin and thrombin-antithrombin complex (TAT). Histopathological diagnosis and 30-day survival were recorded. None of the 15 enrolled dogs had pre-operative sonographic evidence of portal system thrombosis. Three of fifteen dogs were thrombocytopenic, three had thrombocytosis, three were hyperfibrinogenemic, one had low vWF:Ag, three had mild prolongations of PT and none had abnormal aPTT. Based on the TEG G value, 13/15 dogs were hypercoagulable (mean ± SD 13.5 ± 5.4 kd/s). Antithrombin deficiency was identified in 9/15 dogs (mean ± SD 68.7 ± 22.7%) with 5/9 having concurrently elevated TAT suggesting active thrombin generation. No dogs developed portal system thrombosis and all achieved 30-day survival. Pre-operative hypercoagulability was recognized commonly but its association with post-operative thrombosis remains undetermined.